The Effect of Vocabulary Journal on Students' Vocabulary Mastery at SMP Negeri 6 Palu - Siti Mutmaina; Erniwati Erniwati; Maf'ulah Maf'ulah; Mochtar Marhum (Journal of English Language and Education, 2026)
Vocabulary mastery plays an important role in supporting students' English language proficiency; however, evidence regarding the effectiveness of Vocabulary Journal among junior high school students remains limited. A Vocabulary Journal is a learning tool that encourages students to systematically record new words, their meanings, and example sentences to support vocabulary learning. This study aimed to investigate the effect of Vocabulary Journal on the vocabulary mastery of eighth-grade students at SMP Negeri 6 Palu. Employing a quantitative approach with a quasi-experimental non-equivalent control group design, the study involved 72 students selected through cluster random sampling. Data were collected through vocabulary pre-tests and post-tests and analyzed using descriptive and inferential statistics. The findings revealed that the experimental group achieved a higher mean post-test score (66.32) than the control group (52.01). Since the data were not normally distributed, the Mann–Whitney U test was employed, yielding a significant difference between the groups (p = 0.002 0.05). Therefore, Vocabulary Journal can be considered an effective strategy for vocabulary instruction in EFL classrooms.